Mending Wall? The War over History in South Korea - Jeong, Sangjun (Review of International American Studies, 2018)
Sangjun Jeong Seoul National University South Korea Mending Wall? The War over History in South Korea Abstract: Until Korea was divided into North and South in 1945, it had maintained its territorial unity on the Korean peninsula for well over 1,000 years. Then, two young US officers drew an arbitrary line along the 38th parallel. Developing into a heavily militarized zone only several years later, ironically called the De-Militarized Zone (DMZ), that division has lasted for decades and into the present. Recently, several symbolic acts were performed in the zone and innovative plans were suggested to make the land strip into a peace park as a symbol of ideological reconciliation and ecological paradise. Yet to many Koreans, the zone is still inscribed as a wall permanently bisecting the peninsula not only physically but also culturally. Through an analysis of Robert Frost’s poem “Mending Wall,” this article contemplates the divisions within South Korean society over the North –South divide as a war over the telling of history. This history, however told, must be understood alongside the sentiment of han, a Korean word loosely defined as frustration, anger, and sadness, something that has been shaped by centuries of suffering from wars, invasions, colonization, injustice, and exploitation. Keywords: Korean Peninsula, Political Divisions, History, War, Demilitarized Zone